2017
DOI: 10.1371/journal.pone.0180997
|View full text |Cite
|
Sign up to set email alerts
|

Falls, non-accidental falls and syncope in community-dwelling adults aged 50 years and older: Implications for cardiovascular assessment

Abstract: ObjectivesTo calculate the prevalence of all falls, non-accidental falls and syncope in an older population and characterize cardiovascular risk profiles.DesignProspective, longitudinal cohort study.SettingThe first two waves of data from the Irish Longitudinal Study on Ageing (TILDA).Participants8172 community-dwelling adults aged 50 years and older resident in the Republic of IrelandMeasurementsSelf-reported history of all falls, non-accidental falls and syncope in the year preceding the first two waves of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
24
1
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 34 publications
3
24
1
3
Order By: Relevance
“…In the multivariate analysis, antianginals and opioids were significantly associated with falls. These findings were similar to the study by de Jong et al and may be due to sudden hypotension, arrhythmia or a syncopal episode . There was also a significant difference in fear of falls and vision impairment between the groups.…”
Section: Discussionsupporting
confidence: 90%
“…In the multivariate analysis, antianginals and opioids were significantly associated with falls. These findings were similar to the study by de Jong et al and may be due to sudden hypotension, arrhythmia or a syncopal episode . There was also a significant difference in fear of falls and vision impairment between the groups.…”
Section: Discussionsupporting
confidence: 90%
“…The sample in this study reported more falls (34.10 %) than what was previously reported in older adults with CVD 2,31 . In the Cardiovascular Health study, 13.2% of older adults with CVD related risk factors reported falling 31 .…”
Section: Discussioncontrasting
confidence: 53%
“…One out of four older adults falls each year, accounting for more than fifty billion dollars in health care costs 1 . Adults with cardiovascular disease (CVD) are reported to have higher odds of falling as compared to those without reported CVD 2 . A link between cognition and falls/falls risk has been reported in the literature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Particularly, hip fractures are major consequences of syncope-related falls and are associated with approximately 25% reduction of life expectancy and institutionalisation rates ranging between 8% and 34% in community-dwelling patients 26. Differentiation between falls and syncope is challenging, especially among elderly patients with cognitive impairment and experience from dedicated syncope and fall facilities reinforces the evidence of an overlap between these two entities, which are often indistinguishable and likely manifestation of the similar underlying pathophysiology 27. Both non-accidental falls and syncope show strong association with antihypertensive treatment and number of prevalent cardiovascular conditions including atrial fibrillation 27.…”
Section: Discussionmentioning
confidence: 95%